P04.18 Unravelling the tumour microenvironment of glioma. (19th September 2018) - McKelvey, K; Hudson, A; Wheeler, H; Diakos, C; Howell, V
Abstract: Background: With the incidence and mortality of brain cancer almost equivocal there is a vital need to understand the intricacies of the glioma microenvironment. This study details the temporal and spatial localisation of immune cell populations and mediators during glioma development using the murine orthotopic Gl261 glioma model. Material and Methods: Male C57Bl/6 mice were stereo-tactically inoculated with 1x10 6 Gl261 cells at AP0.1mm, ML1.0mm, DV2.4mm Bregma. Immune cell populations were assessed at D0, D1, D3, D7, D14, D21 post-inoculation by veterinary haematological analyser (Coulter Ac·Tdiff™) and 16-parameter flow cytometry (Fortessa™). Results: Significant temporal changes were observed in all immune cell populations among the splenic, bone marrow and peripheral blood systemic compartments: WBCs, RBCs, platelets, CD3+ T cell, CD3+CD4+ Th, CD3+CD4+CD25+ Treg, CD3+CD8+ Tc, NK1.1+ NK, NK1.1+CD3+ NK/T, CD115+CD11b+ monocyte, CD115+CD11b+CD80+ M1, CD115+CD11b+CD206+ M2, CD115-CD11b+ DC, CD115-CD11b+Ly6ChighLy6G- M-MDSC, CD115-CD11b+Ly6C+Ly6G+ PMN-MDSC, CD117+ HSC and CD19+ B cell (Kruskal-Wallis with Dunn's multiple comparison test; p=0.02- p<0.0001). Analysis of plasma coagulation and inflammatory mediators, and histopathology of the tumour microenvironment is to be completed. Conclusion: The data derived provides baseline characteristics to study the changes associated with radiation, chemotherapy and immunotherapy treatment and to sequence therapies to maintain immune modulation. This information will contribute to identifying those immunotherapies which will have maximal benefit among the glioma patient population, where currently anti-CTLA-4 and anti-PDL-1 immunotherapies have had little impact. KM is supported by a Matt Callander Beanie for Brain Cancer HMRI Fellowship funded by the Mark Hughes Foundation, and grants from The Brain Cancer Group and Sydney Vital Translational Cancer Centre; AH is supported by a The Brain Cancer Group Fellowship.